Pengaruh Quick Ratio (QR), Debt To Assets Ratio (DAR) Dan Earning Per Share (EPS) Terhadap Return Saham Perusahaan Manufaktur Subsektor Otomotif Dan Komponen Yang Terdaftar Di BEI - Dian Ayu Andriani; Zulfa Khairina Batubara; Nisfu Fhitri; Dandy Gunawan Sinaga (Politeknik Ganesha Medan, 2024)
This study aims to determine whether there is an Influence of Quick Ratio, Debt to Assets Ratio and Earning Per Share on Stock Returns of Automotive and Component Manufacturing Companies Listed on the Indonesia Stock Exchange. The population in this study is the Automotive and Component Manufacturing Companies Listed on the Indonesia Stock Exchange. The sample taken using Purposive Sampling. So that 40 observations were obtained as samples. Based on the results of the study, it can be concluded that partially Quick Ratio and Earning Per Share have an effect on Stock Returns. While Debt to Assets Ratio does not affect Stock Returns. Simultaneously Quick Ratio, Debt to Assets Ratio and Earning Per Share have an effect on Stock Returns of Automotive and Component Manufacturing Companies Listed on the Indonesia Stock Exchange. The results of this study indicate that Quick Ratio (QR), Debt to Assets Ratio (DAR) and Earning Per Share (EPS) simultaneously or together are able to provide a significant influence on Stock Returns in the Automotive and Component Manufacturing Subsectors Listed on the Indonesia Stock Exchange.